Evaluation of the Flagship Qur'an Memorization Program Using the Countenance Stake Model: Challenges and Opportunities for Development - Ashri Nafiah Nur Isti Qomah; Muhammad Rafif Yuliza Absa; Muhammad Iqbal Al Fatih; Junita Evie Puhan; Istanto Istanto; Muh Nur Rochim Maksum (Journal La Edusci, 2026)
This study aims to evaluate the implementation of the Superior Tahfidz Program at MI Muhammadiyah Tahfidzul Qur'an Matesih using the Countenance Stake Model which assesses three main components, namely antecedent, transaction, and outcome. The evaluation was conducted to determine the level of program readiness, the suitability of the implementation process with the planning, and the achievement of results obtained through Tahfidz activities. Data collection was carried out through documentation, observation, interviews, and review of student memorization achievements, which were then analyzed descriptively through a comparison between intents and observations according to the structure of the evaluation model. The study results indicate that the Superior Tahfidz Program has a clear planning basis, adequate institutional support, and a curriculum structure that supports the formation of a Qur'anic culture in madrasas. During the implementation phase, the program ran fairly consistently with its initial objectives, although several challenges were still encountered, such as variations in student abilities, limited learning time, and the need to improve the capacity of Tahfidz teachers. Meanwhile, the outcome component shows that the program has a positive contribution to the development of memorization and religious character of students, although its effectiveness depends on the continuity of guidance and strengthening collaboration between teachers, madrasas, and parents. Further analysis revealed opportunities for program development, particularly through improved learning methods, the use of supporting media, and strengthening the memorization evaluation system